A Study of University of Idaho "Ag News" Published by Idaho Newspapers in 1984 and 1985 - Marlene A. Fritz (Journal of Applied Communications, 1987)
In 1984-86, the University of Idaho Agricultural Communications Center evaluated the extent to which news releases are used by Idaho newspapers and attempted to determine whether any of the variables used to describe a story enhanced its use.